A novel glycyrrhizin acid-coated stent reduces neointimal formation in a rabbit iliac artery model - Teng, Shuai; Zhu, Zhaowei; Li, Yang; Hu, Xinqun; Fang, Zhenfei; Liu, Zhenjiang; Zhou, Shenghua (Frontiers in Pharmacology, 2023)
Introduction: Most drug-eluting stents (DESs) inhibit intimal hyperplasia but impair re-endothelialization. This study aimed to evaluate in vivo strut coverage and neointimal growth in a new glycyrrhizin acid (GA)-eluting stent. Methods: New Zealand White rabbits (n = 20) with atherosclerotic plaques were randomly divided into three groups based on implanted iliac artery stents: bare-metal stents (BMSs), rapamycin-eluting stents, and GA-eluting stents. After the in vivo intravascular ultrasound (IVUS) assessment at 28 days, the vessels were harvested for scanning electron microscopy (SEM) and histology. After 4 weeks of follow-up, the stent and external elastic lamina (EEL) areas were compared among the groups. Results: The rapamycin- or GA-eluting stents significantly reduced the neointimal area compared with BMSs, though GA-eluting stents had the lowest reduction. There were more uncovered struts for rapamycin-eluting stents than those for GA-eluting stents and bare-metal stents. The endothelial nitric oxide synthase (eNOS) expression in GA-eluting stents was much higher than that in BMSs and rapamycin-eluting stents, even though the endothelial coverage between struts was equivalent between BMSs and GA-eluting stents. Moreover, GA-eluting stents markedly promoted re-endothelialization and improved arterial healing compared to rapamycin-eluting stents in a rabbit atherosclerotic model. Conclusion: In conclusion, the novel GA-coated stent used in this study inhibited intimal hyperplasia and promoted re-endothelialization.